Potentially morally injurious experiences and associated factors among Dutch UN peacekeepers: a latent class analysis - Mariëlle L. de Goede; Niels van der Aa; Trudy M. Mooren; Miranda Olff; F. Jackie June ter Heide (European Journal of Psychotraumatology, 2024)
Background: During peacekeeping missions, military personnel may be involved in or exposed to potentially morally injurious experiences (PMIEs), such as an inability to intervene due to a limited mandate. While exposure to such morally transgressive events has been shown to lead to moral injury in combat veterans, research on moral injury in peacekeepers is limited.Objective: We aimed to determine patterns of exposure to PMIEs and associated outcome- and exposure-related factors among Dutch peacekeepers stationed in the former Yugoslavia during the Srebrenica genocide.Method: Self-report data were collected among Dutchbat III veterans (N = 431). We used Latent Class Analysis to identify subgroups of PMIE exposure as assessed by the Moral Injury Scale–Military version. We investigated whether deployment location, posttraumatic stress disorder (PTSD), posttraumatic growth, resilience, and quality of life differentiated between latent classes.Results: The analysis identified a three-class solution: a high exposure class (n = 79), a moderate exposure class (n = 216), and a betrayal and powerlessness-only class (n = 135). More PMIE exposure was associated with deployment location and higher odds of having probable PTSD. PMIE exposure was not associated with posttraumatic growth. Resilience and quality of life were excluded from analyses due to high correlations with PTSD.Conclusions: Peacekeepers may experience varying levels of PMIE exposure, with more exposure being associated with worse outcomes 25 years later. Although no causal relationship may be assumed, the results emphasize the importance of better understanding PMIEs within peacekeeping.